Photographic scale for the characterization of actinic keratosis through reflectance confocal microscopy: a quantitative approach to cellular transformation - Guerra, Lucas Offenbecker; Leão Santos, Ana Carolina; Cortinoz, Janaina Rosa; Magalhães, Renata Ferreira; Vasques, Louise Idalgo; Leonardi, Gislaine Ricci (Frontiers in Medicine, 2024)
Background: Actinic keratosis (AK) is a highly prevalent pre-cancerous skin lesion that often leads to cutaneous squamous cell carcinoma. There are different stages of evolution of the disease and several features that characterize keratosis. This study aimed to develop a qualitative and quantitative visual diagnostic tool to facilitate the identification of the characteristics and severity of the main cellular attributes of AK and to show its applicability in evaluating the evolution or treatment through image analysis. Methods: Literature research on the main scientific databases and in the institute’s database was carried out to gather all the different tecidual transformation levels of the attributes previously described for AK. To validate the scale, a preliminary characterization study was carried out with 21 subjects who had clinically diagnosed AK lesions to classify the attributes in each skin layer and test the accuracy of the diagnosis of the scale. Afterward, and to show the possibility of a follow-up with a topical treatment, the subjects were divided into two treatment groups, receiving either a cream formulation containing retinoic acid, or a placebo formula. The evaluation was carried out through Confocal Reflectance Microscopy and a digital camera with dermoscopic quality before and after 90 days of treatment Results: A table detailing the 18 attributes of AK, and a photographic scale containing RCM images graded by scores established for each characteristic and the frequency of spreading were developed. The results of the validation presented good repeatability, correlation with clinical evaluation, and capacity for differentiating treatments demonstrated by the significant improvement after topical treatment by the reduction of the score for 10 out of the 18 attributes. The preliminary study, evaluated by the detailed transformation scale highlights important differences in the subclinical approach that allows a deeper evaluation of the aspects of the lesion's reincidence even after fully treated skin sites. Conclusions: This study brings an innovative method based on RCM, to assist in the quantification of cell transformation level, provide early diagnosis, and deliver a powerful treatment evaluation tool to provide smoother treatment, as well as prevent re-incidence in the cases.